(untitled) (Journal of Atomic, Molecular, Condensed Matter and Nano Physics, 2022)
We report the optically stimulated luminescence of Eu\(^3+\) doped NaLi\(_2\)PO\(_4\) synthesized by solid state diffusion method which is crushed and sieved further using Ball milled for different time period (1 to 10 days) with different particle sizes ranging from micro to nano sizes are obtained. Formation of the material was confirmed by XRD analysis and matched peak to peak with JCPDS#80-2110. Scanning electron microscope (SEM) images were used for determining its particle size(s). Optically stimulated luminescence (OSL) characteristics were studied to see the effect of particle size after irradiating with \(γ\)-rays from Co\(^60\) source for wide dose range (10 Gy-100 KGy). It was found that OSL sensitivity depends on particle size of the material. Easy method of synthesis, good sensitivity, low fading, good chemical stability, etc. make this OSLD nano phosphor a good candidate for radiation dosimetry using OSL.